Analysis of Jakarta’s Mass Rapid Transit Infrastructure Services on Passenger Satisfaction Performance With The Influence of The Covid 19 Virus - Sunandar Ali; Mukhlisoh Mukhlisoh; Sumiyati Sumiyati (LPPM NAROTAMA UNIVERSITY, Indonesia, 2021)
Service quality is a strategy that is very important for the development and success of business organizations. The purpose of this study is to analyze the dominant variables in MRT Jakarta infrastructure services on customer satisfaction performance and to find solutions to the dominant variables found. The hypothesis of this research is whether or not there is an effect of MRT Jakarta infrastructure services on customer satisfaction performance with the Covid 19 pandemic. The results obtained through the analysis of the Customer Satisfaction Index (CSI) were 85.38% and stated that customers were very satisfied with the MRT Jakarta services provided. In the Importance Performance Index (IPA) analysis with a Cartesian diagram, there are three dominant variables of MRT Jakarta services on customer satisfaction performance. Judging from the level of performance and importance of the quality of MRT Jakarta services, on average, it is good, so that the MRT Jakarta management must prioritize several variables to be improved and maintain those variables that are considered to be in accordance with customer expectations.